Studies on Homalomeneae (Araceae) of Sumatera III – A new species of Furtadoa–Furtadoa indrae - Boyce, P.C; Wong, Sin Yeng (International Aroid Society, Inc., 2016)
Furtadoa indrae P.C.Boyce & S.Y.Wong, is described as a taxonomically novel species from Riau Province, Sumatera, and compared with the most similar species, West Sumateran F. sumatrensis M.Hotta. An identification key to the described species of Furtadoa is provided. Furtadoa indrae is figured in colour from living plants, and a comparative figure of the spadix of all three described Furtadoa species is presented.